The red bicycle : the extraordinary story of one ordinary bicycle - Isabella, Jude.; Shin, Simone (Toronto, ON : Kids Can Press, 2015)
When Leo outgrows his red bicycle, he sends it to Burkina Faso, where it starts a journey through many hands and has many uses. Includes information about how to get involved in bicycle donation efforts.
Includes bibliographical references (p. 30-31).
School Library Journal, March 2015
Publisher's Weekly, January 2015
Booklist, February 2015
New York Times, May 2015
Horn Book, May 2015
Keywords: Bicycles -- Fiction; Bicycles -- Burkina Faso -- Fiction; Altruism -- Fiction; Helping behavior -- Fiction